2018
DOI: 10.1530/eje-17-0810
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum, incidence, kinetics and management of endocrinopathies with immune checkpoint inhibitors for metastatic melanoma

Abstract: Combination immunotherapy has a greater risk of development of endocrinopathy compared to anti-PD-1 monotherapy. Regular biochemical profiling of patients, particularly within the first twelve weeks, results in early detection of endocrinopathy to minimise morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
81
6
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 28 publications
11
81
6
6
Order By: Relevance
“…None of the 26 patients recovered from central hypoadrenalism during a median follow‐up of 15 months, as likewise reported in previous studies, while recovery from central hypothyroidism occurred in almost all patients. Similarly, to our results, Albarel et al described resolution of central hypothyroidism in 11/13 patients, while Scott et al reported the same in 0/10 patients. Of note, Min et al reported recovery in 14 of 22 patients in a median of 10 weeks.…”
Section: Discussionsupporting
confidence: 86%
“…None of the 26 patients recovered from central hypoadrenalism during a median follow‐up of 15 months, as likewise reported in previous studies, while recovery from central hypothyroidism occurred in almost all patients. Similarly, to our results, Albarel et al described resolution of central hypothyroidism in 11/13 patients, while Scott et al reported the same in 0/10 patients. Of note, Min et al reported recovery in 14 of 22 patients in a median of 10 weeks.…”
Section: Discussionsupporting
confidence: 86%
“…In any case, these data need to be taken with caution, because the age of occurrence and the sex ratio can be very different from one cancer to another (melanoma or non-small-cell lung cancer for example). The median time to occurrence is, as in this case report, between 2 and 4 months (range 4 weeks to 19 months) with anti-CTLA-4 (20,22,23,24), from 3 to 6 months with PD-1 or PD-L1 (25,26) and earlier for those on combination treatment (30 days on average) (13). It should also be noted that the development of autoimmune disease has been shown to correlate with a better response to ipilimumab therapy, especially in grade 3/4 IRAEs (6,27,28).…”
Section: Is Hypophysitis a Common Adverse Event With Immunotherapy?supporting
confidence: 68%
“…Therefore, patients treated with PD-1 inhibitors or PD-L1 inhibitors appear to more frequently develop thyroid dysfunction than hypophysitis. In this study, it is worth noting that combination treatments enhanced the prevalence of all types of endocrine IRAEs and that these also occurred earlier (12,13). The incidence of confirmed primary adrenal insufficiency is very low (case reports) and can occur with both anti-CTLA-4 and PD-1 inhibitors (12).…”
Section: Is Hypophysitis a Common Adverse Event With Immunotherapy?mentioning
confidence: 76%
“…Almost 90% of TAEs arose within the first 3 months, and none were found after 9 months. This finding is in line with previous reports showing time to onset of thyroid dysfunction of between 6 and 9 weeks . In accordance with the literature, time to thyrotoxicosis onset was shorter than for hypothyroidism; the median time for hyperthyroidism to evolve to hypothyroidism is known to be very short and was <45 days in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, thyroid disorders are becoming more prevalent in this population, representing a challenge for oncologists, endocrinologists and general practitioners alike. 14 In the present study, 23% of patients presented TAEs, as previously reported in some studies. 15,16 Current literature data are conflicting.…”
Section: Discussionsupporting
confidence: 89%